PENGARUH KEBIJAKAN DIVIDEN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 – 2018 - Mulia Rahmah, S. Kom., M.Si.; Alifia Febriani (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
The influence of Dividend Policy and Company’s Size on The Value of the Company of Manufacturing Companies in consumer goods industri Sector Listed on the Indonesia Stock Exchange 2015-2018. This research aims to examine The influence of Dividend Policy and Company’s Size on The Value of The Company of Manufacturing Companies in consumer goods industri Sector Listed on the Indonesia Stock Exchange 2015-2018. The research was conducted in consumer goods industry sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the 2015-2018 period. The sampling method used was purposive sampling method, the sample used was 14 companies. The data analysis technique used is descriptive statistics, classic assumption test, normally test, multicolonierity test, autocorrelation test, heteroscedasticity test, multiple liner regression model and hypothesis testing using SPSS 22  for windows. The result showed that Dividend Policy and Company’s Size has simultaneously affect The Value of The Company. In Parsial, The Dividend Policy has a positive and significant effect on The Value of The Company.Meanwhile, the Company Size has a negative but unsignificant effect on The Value of The CompanyThe influence of Dividend Policy and Company’s Size on The Value of the Company of Manufacturing Companies in consumer goods industri Sector Listed on the Indonesia Stock Exchange 2015-2018. This research aims to examine The influence of Dividend Policy and Company’s Size on The Value of The Company of Manufacturing Companies in consumer goods industri Sector Listed on the Indonesia Stock Exchange 2015-2018. The research was conducted in consumer goods industry sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the 2015-2018 period. The sampling method used was purposive sampling method, the sample used was 14 companies. The data analysis technique used is descriptive statistics, classic assumption test, normally test, multicolonierity test, autocorrelation test, heteroscedasticity test, multiple liner regression model and hypothesis testing using SPSS 22  for windows. The result showed that Dividend Policy and Company’s Size has simultaneously affect The Value of The Company. In Parsial, The Dividend Policy has a positive and significant effect on The Value of The Company.Meanwhile, the Company Size has a negative but unsignificant effect on The Value of The Company    The influence of Dividend Policy and Company’s Size on The Value of the Company of Manufacturing Companies in consumer goods industri Sector Listed on the Indonesia Stock Exchange 2015-2018. This research aims to examine The influence of Dividend Policy and Company’s Size on The Value of The Company of Manufacturing Companies in consumer goods industri Sector Listed on the Indonesia Stock Exchange 2015-2018. The research was conducted in consumer goods industry sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the 2015-2018 period. The sampling method used was purposive sampling method, the sample used was 14 companies. The data analysis technique used is descriptive statistics, classic assumption test, normally test, multicolonierity test, autocorrelation test, heteroscedasticity test, multiple liner regression model and hypothesis testing using SPSS 22 for windows. The result showed that Dividend Policy and Company’s Size has simultaneously affect The Value of The Company. In Parsial, The Dividend Policy has a positive and significant effect on The Value of The Company.Meanwhile, the Company Size has a negative but unsignificant effect on The Value of The Company